Analysis Of Soap, Kie, And Icd X Writing Completeness In Medical Records At General Poly And Maternal And Child Health Family Planning - Hafifah Hafifah; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The health service information system in individual health efforts consists of a clinical information system, a health service administration system, a health service support system, and a health service decision support system. The aim of this research is to analyze the completeness of writing SOAP, KIE and ICD. This research is a descriptive study with a cross sectional research design which was carried out at the Darussalam Health Center in Medan in June-August 2022. The sample size was determined using the Slovin formula, namely the number of data listed was 3772 data and the data used as a sample was 97 samples. Data were analyzed using descriptive survey univariate analysis and bivariate analysis with the chi-square test. The results of the research were that the majority of SOAP fillings in General Poly and Maternal And Child Health Family Planning were fully filled, the majority of ICD fillings in General Poly and Maternal And Child Health Family Planning were fully filled, the majority of ICD X filling in General Poly and Maternal And Child Health Family Planning were fully filled. - Maternal And Child Health Family Planning is not complete, there is no increase in filling in the requirements for SOAP, IEC and ICD X at the General Poly and Maternal And Child Health Family Planning Poly. The suggestion in this research is that the results of this research can be used as input for conducting evaluations and training for all employees so that there will be improvements in writing clinical documentation.Keywords: General poly, Maternal And Child Health Family Planning, Medical records